2019
DOI: 10.1126/science.aat0778
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase USP10 regulates Notch signaling in the endothelium

Abstract: Deubiquitinase fine-tunes Notch signaling The branching of blood vessels is controlled in part by signaling through Notch receptor proteins. When NOTCH1 binds its ligand DLL4, the intracellular domain (NICD1) is cleaved from the receptor and works with other proteins to regulate gene transcription. In a screen for proteins that interacted with NICD1 in human cells in culture, Lim et al. identified the deubiquitinase USP10. NICD1 is rapidly ubiquitinated and degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…The Notch pathway is a well-ordered, evolutionary conserved pathway and crucial to the regulation of morphological development in multicellular organisms that governs connections between interacting cells (12,13). Dysregulation in Notch signaling transduction is related to various genetic diseases, including cancers (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The Notch pathway is a well-ordered, evolutionary conserved pathway and crucial to the regulation of morphological development in multicellular organisms that governs connections between interacting cells (12,13). Dysregulation in Notch signaling transduction is related to various genetic diseases, including cancers (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, myocardial fibrosis in perivascular and interstitial spaces were significantly increased in USP10-CKO mice ( Zhang et al, 2020 ). Research on the endothelium revealed that USP10, as a regulatory protein, delayed the rate of NICD1 degradation by deubiquitinating the Notch1 receptor ( Lim et al, 2019 ). Consistent with the above findings, we further examined the changes in FSTL1 and USP10 in T2DM with and without MI and investigated the relationship between FSTL1 and USP10/Notch1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-specific protease 10 (USP10) is a deubiquitinase that catalyzes the hydrolysis reaction and removes conjugated ubiquitin from its target proteins. In response to cell stress, USP10 was translocated from the cytoplasm to the nucleus to regulate cell cycle and apoptosis ( Lim et al, 2019 ; Zhang et al, 2020 ). Previous studies demonstrated that USP10 protected cells against pathological injury in numerous organs ( Yuan et al, 2010 ; Deng et al, 2016 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deubiquitination mediated by many deubiquitinases (DUBs) regulates the level of substrate proteins by cleaving ubiquitin chains and participates in a variety of cellular processes [ 3 , 4 ]. DUBs play a role in tumour metastasis progression [ 5 ], including degradation of extracellular matrix [ 6 ], epithelial–mesenchymal transition [ 7 ], angiogenesis [ 8 , 9 ], circulating tumour cell behaviour [ 10 ], anoikis resistance [ 11 ] and so on. Proteasome and ubiquitin E3 ligase inhibitors and first-generation DUB inhibitors are now approaching clinical trials [ 12 ].…”
Section: Introductionmentioning
confidence: 99%